Pengembangan Media Power Point Interaktif Dalam Mata Pelajaran Ilmu Pengetahuan Sosial - Syahda Naila Rahma; Erwin Saputra (Jurnal Riset Madrasah Ibtidaiyah, 2023)
Learning media is one of the most important components in the learning process. The existence of media can color and make students more active and enthusiastic in learning. However, in reality there are still few teachers who use media in their learning process, causing student learning outcomes to decrease. This study aims to describe the design and determine the feasibility of developing interactive PowerPoint learning media in social studies subjects. The research model used is 4D (Define, Design, Develop, Disseminate). Methods of data collection, namely observation, interviews and questionnaires / questionnaires. Technical analysis of data using descriptive qualitative through observation and questionnaires/questionnaires. The research subjects were 23 students of class IV of Public Elementary Schools in the even semester, 2023/2024 academic year. The results of the observation show that the use of interactive power point media in social studies lessons can increase the focus and activeness of the participants. Student responses from the questionnaires that were distributed also received positive results. In fact, the existence of this media can improve student learning outcomes. Therefore, this Interactive Power Point Media is declared feasible and has been validated by several experts. Thus, teachers are expected to always strive for improvement in the learning process so that students' abilities and experiences can increase.